Using Evidence From Voluntary Fisheries Data Collection Programmes to Support Marine Spatial Planning and Resolve Multiple-Use Conflicts - Dosell, Abbie; Edwards, Dan; Gregory, Amanda; Ponteen, Alwyn; O’Garro, Joseph; Cornick, Laura; Hawkridge, Jane M. (Frontiers in Marine Science, 2021)
Natural disasters have altered the landscape of Montserrat’s marine environment significantly over the past 30 years, forcing rapid adaptation of marine species and the human population that relies upon them. Volcanic activity has led to an abundance of volcanic sediment, which has seen rise to the expansion of the island’s sand mining and aggregate industry. Similarly, a series of volcanic eruptions has resulted in smothered fishing grounds and maritime exclusion zones, increasing the pressure on the remaining accessible marine environment. Recent increases in shipping activity, due to the expanding aggregate sector, partnered with a lack of official marine spatial planning, has led to the west coast of the island becoming a stakeholder conflict hotspot. Regular interactions between fishing gear and shipping vessels were resulting in damaged and lost fish pots and causing physical damage and increased ghost-fishing on the coral reefs, with additional impacts on fisher livelihoods. This paper builds upon earlier work in Montserrat to engage fishers in fisheries data collection programmes. Here we use data from Montserrat’s fishing fleet to understand the distribution and intensity of fish pot activity within the conflict area. Maximum activity was distributed along the edge of the reef front, near the drop-off, with the greatest intensity towards the south. These data, and outcomes from stakeholder consultation, have allowed the relevant authorities and decision-makers to identify a suitable shipping route that avoids pot-based fishing grounds, while remaining as close inshore as feasible, to avoid unnecessary fuel costs for shipping vessels. As a result, the Montserrat Port Authority has implemented a restricted area around the identified fishing grounds, in which commercial vessels are not allowed to transit. This intervention represents a ‘win-win’ solution, reducing the risk of commercial vessel-fishing gear conflict in the southwestern pot-based fishing grounds, without substantially increasing the burden of excess travel on commercial vessels. Here we show how engagement with the fishing community and voluntary participation in data collection has supported a conflict resolution deemed suitable to both parties; allowing the needs of the smaller traditional fishing sector to influence management of the rapidly expanding, high value aggregate sector.